Bioinspired Total Synthesis of Montanine‐Type Amaryllidaceae Alkaloids1. Issue 52 (8th November 2013) - Bao, Xu; Cao, Ye‐Xing; Chu, Wen‐Dao; Qu, Hu; Du, Ji‐Yuan; Zhao, Xian‐He; Ma, Xiao‐Yan; Wang, Cheng‐Tao; Fan, Chun‐An
<x xml:space="preserve">Abstract</x> Finding a common path: A synthetic strategy inspired by the proposed biogenesis of the montanine‐type alkaloids enabled the concise asymmetric synthesis of these compounds in a divergent fashion on the basis of an unprecedented tandem oxidative dearomatization/intramolecular aza‐Michael addition as the key step. This bioinspired approach revealed a chemical connection between the cherylline‐ and montanine‐type alkaloids (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>